Policy Approaches to Climate Change in Mineral Rich Countries - Sekar, Sri (World Bank, Washington, DC, 2019)
The green economy entails an approach by nations to adopt economic policies designed to develop climate-sensitive industrial sectors that can drive long-run sustainable economic growth. Any meaningful transition to a new green economy will require the mining sector as a central stakeholder. This is in part due to the significance of the minerals sector to the overall global economy. Minerals make up and will continue to make up the fundamental building blocks of the global economy. This report provides an overview of the policies of countries leading the shift toward a green economy, and the implications of those policies for the mining sector in those countries.